Framing social security reform: Behavioral responses to changes in the full retirement age - Luc Behaghel; David M. Blau (Institute for the Study of Labor (IZA), 2010)
We use a US Social Security reform as a quasi-experiment to provide evidence on framing effects in retirement behavior. The reform increased the full retirement age (FRA) from 65 to 66 in two month increments per year of birth for cohorts born from 1938 to 1943. We find strong evidence that the spike in the benefit claiming hazard at 65 moved in lockstep along with the FRA. Results on self-reported retirement and exit from employment are less clearcut, but go in the same direction. The responsiveness to the new FRA is stronger for people with higher cognitive skills. We interpret the findings as evidence of reference dependence with loss aversion. We develop a simple labor supply model with reference dependence that can explain the results. The model has potentially important implications for framing of future Social Security reforms.
Keywords: J26; 330; retirement; social security; loss aversion